Anemia in inhabitants of Caceres/MT and its correlation with income per capita - Sanches, E.M.C.; Barros, M.D. de; Mello, P.R.B. de (Revista do Instituto de Medicina Tropical de São Paulo, 1988)
A study was made about anemia and its relationship with the income/per capita among 1178 individuals between the age of 6-14 years old (of both sex), 15 to 45 years old female, 15 to 45 years old male. It showed higher prevalence of anemic individuals belonging to the income ranges of 1/4 minimum salary and 1/4 – 1/2 minimum salary within the three ranges of ages studied. It was observed a statistical relationship between the income/per capita and the average rates of hemoglobin for the three ranges of age.